LAW ENFORCEMENT AGAINST PERPETRATORS OF UNLICENSED GOLD MINING CRIME IN SANGIHE ISLANDS - Susetyo, Tony Budi; Amiq, Bahrul; Prawesthi , Wahyu (IUS POSITUM: Journal of Law Theory and Law Enforcement, 2023)
Law No. 4/2009 on Minerals and Coal prohibits unlicensed gold mining activities because they have a big potential impact on environmental damage. Therefore, strict law enforcement is needed against humans who are not aware of environmental damage. The main problem in this research is the criminal provisions and law enforcement against perpetrators of unlicensed gold mining in the jurisdiction of the Sangihe Islands Police, North Sulawesi. The objective of this research is to find out the law enforcement process against perpetrators of unlicensed gold mining crimes in the jurisdiction of the Sangihe Islands. The approach method used in this research is the sociological juridical approach method. The juridical sociological approach is a research approach that uses legal aspects (legislation and facts in the field) related to the subject matter to be discussed, associated with the reality in the field or examines the positive law of an object of research and sees the practices that occur there. There are many mining businesses in various regions in Indonesia that are managed by local communities. Unfortunately, although there are national regulations that regulate the mining business, there are still very many mines managed by the community that have the status of illegal mining because they do not have a license, either a Special Mining Business License (IUPK) or other permits.